Phytochrome phosphorylation in plant light signaling - Han, Yun-Jeong; Kim, Seong-Hyeon; Kim, Jeong-Il (Frontiers in Plant Science, 2024)
Plant phytochromes, renowned phosphoproteins, are red and far-red photoreceptors that regulate growth and development in response to light signals. Studies on phytochrome phosphorylation postulate that the N-terminal extension (NTE) and hinge region between N-and C-domains are sites of phosphorylation. Further studies have demonstrated that phosphorylation in the hinge region is important for regulating protein-protein interactions with downstream signaling partners, and phosphorylation in the NTE partakes in managing phytochrome activity for signal attenuation and nuclear import. Moreover, phytochrome-associated protein phosphatases have been reported, indicating a role of reversible phosphorylation in phytochrome regulation. Furthermore, phytochromes exhibit serine/threonine kinase activity with autophosphorylation, and studies on phytochrome mutants with impaired or increased kinase activity corroborate that they are functional protein kinases in plants. In addition to the autophosphorylation, phytochromes negatively regulate PHYTOCHROME-INTERACTING FACTORs (PIFs) in a light-dependent manner by phosphorylating them as kinase substrates. Very recently, a few protein kinases have been also reported to phosphorylate phytochromes, suggesting new views on the regulation of phytochrome via phosphorylation. Using these recent advances, this review details phytochrome regulation through phosphorylation and highlights their significance as protein kinases in plant light signaling.